Labour disputes and the game of legal representation - Henri Fraisse (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper explores the prisoner's dilemma that may result when workers and firms are involved in labour disputes and must decide whether to hire a lawyer to be represented at trial. Using a representative data set of labour disputes in the UK and a large population of French unfair dismissal cases, we find that a lawyer substantially increases the firm's probability of winning at trial but has little effect on the worker's victory probability. The UK data contain award and litigation costs and allow us to compute the pay-off matrix. We do not find evidence of a prisoner's dilemma, given that the total pay-off for the worker is not significantly different whether she is represented or not. Surprisingly, the dominant strategy for the firm is not to be represented.
Keywords: J52; J53; K41; 330; litigation; lawyers; labour dispute resolution; prisoner's dilemma; Arbeitskonflikt; Rechtsberatung; Gefangenendilemma; Zivilprozess; Theorie; Großbritannien; Frankreich